(untitled) (Eurasian Research Bulletin, 2023)
The article provides information about the potential of ecotourism in our Republic and its current opportunities, as well as the touristic opportunities of Yakkabog district of Kashkadarya region. It was found that studies on the development of ecotourism in the region are almost not conducted, even scientific information is almost non-existent. The reason why it was chosen as a research object was the establishment of forestry in Yakkabog district and the fact that it consists of arable lands. Information about the location of Yakkabog district, natural climatic conditions, the influence of the location of the area and the distance from the seas and oceans on the climatic conditions and other factors are given. It is very important to carry out ecotourism in this area, in which employment of the local population and expansion of private hotel development opportunities have been researched